Promoting Learners’ Autonomy in Indonesian EFL Speaking Classes: A Framework for Effective Self-Assessment - Taufiqulloh; Rosdiana, Ihda; Jamaludin, Sanday; Agustia Nindya, Meyga (LPPM Universitas Pancasakti Tegal, 2022)
The role of self-assessment has grabbed much attention in recent years owing to the growing emphasis on independent learning to promote learners’ autonomy which becomes the trend of present-day EFL teaching. Learners' autonomy is an inevitability and has proved to positive effect on EFL learning outcomes. In the Indonesian EFL context, self-assessment used in speaking class seems attention-grabbing to be noticed, while in fact, the majority of Indonesian EFL teachers appear troublesome to provide a method to assess students’ speaking skills. This present study thus aimed to provide a theoretical framework for the effective self-assessment for the Indonesian EFL speaking classes by presenting alternatives of instruments that can be utilized for promoting learners’ autonomy. A descriptive qualitative approach was used in this study using library research through conducting a comprehensive search of the relevant theories and empirical findings related to the self-assessment instrument in EFL speaking class. The result of the analysis shows that several instrument models can be utilized for EFL speaking classes, namely self-assessment checklists and learning logs.